The Evolution of Payments: Traditional Bill Methods Compared to Mobile Innovations - N.B. Mahesh Kumar (International Journal of Mobile Computing Technology, 2025)
"Mobile Payment Experiences in the Future" explores the transformative impact of emerging technologies: Artificial Intelligence (AI), 5G connectivity, and biometrics, on the evolution of mobile payment systems, moving beyond today's simple "tap and pay" solutions. As mobile payments become an essential component of global commerce, these innovations are set to redefine the payment landscape by enhancing transaction speed, security, and personalization. AI will enable real-time fraud detection, adaptive user verification, and customized financial insights, facilitating a seamless and intelligent payment experience. Meanwhile, 5G’s ultra-low latency and high bandwidth will support faster, real-time transactions, paving the way for innovations such as augmented reality (AR) shopping and voice-activated payments. Biometrics, including facial recognition, fingerprint scanning, and behavioral analytics, will introduce advanced layers of security, ensuring safer and more frictionless transactions. This study examines both the technical and social implications of these advancements, envisioning a future where mobile payments are faster, more secure, and deeply integrated into users’ lifestyles. Through case studies and expert insights, we highlight the potential of AI, 5G, and biometrics to revolutionize mobile payments and drive the global transition to a cashless society.
Keywords: 5G connectivity; Artificial Intelligence (AI); Mobile payment; augmented reality (AR); cash payments; security